Assessment of Ruthenium Dye N719 Adsorption Kinetics in Mesoporous TiO2 Films of Dye-Sensitized Solar Cells via Nanoplasmonic Sensing - Fahd M. Rajab (Journal of Nanotechnology)
A dye monolayer formation on a semiconductor surface is critical for efficient dye-sensitized solar cells. The role of dye is to absorb light and convert it to photoelectrons, which are injected into the semiconductor conduction band as device current. We measured dye N719 adsorption via optical techniques including indirect nanoplasmonic sensing. The adsorption rate constant of dye N719 in mimic TiO2 photoelectrodes is determined as ka = 983 M−1 s−1. Dye adsorption for ruthenium dyes N3, N749, and Z907, coated onto TiO2 photoelectrodes of varying thicknesses ranging from 3 μm to 10 μm, was conducted and related to fabricated dye-sensitized solar cell efficiency. Analytical studies included scanning electron microscopy and ellipsometry, X-ray diffraction, and UV-Vis spectroscopy, as well as quantum efficiency and current-voltage device characterizations. The results show greatest enhancement of device performance for dye N719 in spite of multilayer formation, which often is underestimated when addressing the dynamic competing factors that reverse thick-film device performance.